Amperometric sensing and photocatalytic properties under sunlight irradiation of a series of Keggin–AgI compounds through tuning single and mixed ligands. Issue 21 (10th May 2018) - Tian, Aixiang; Liu, Jiani; Li, Tingting; Tian, Yan; Liu, Guiying; Ying, Jun
Abstract : In this work, we synthesized eight compounds based on Keggin anions and Ag I ions by introducingL a andL b . Abstract : By using a single conjugate ring-rich ligandL a orL b and mixed ligandsL a /L b, eight Keggin–Ag I -based compounds, namely [Ag4 L a 5 (SiW12 O40 )]·28H2 O (1 ), [Ag3 L a 4 (PW12 O40 )] (2 ), [Ag3 L a 2 (H2 O)(PW12 O40 )] (3 ), [Ag4 L b 4 (SiW12 O40 )] (4 ), [Ag3 KL b 4 (SiW12 O40 )]·H2 O (5 ), [Ag6 L b 6 (PMo12 O40 )2 ] (6 ), [Ag4 L a L b 3 (C14 H10 O2 )(SiW12 O40 )]·8H2 O (7 ) and [Ag4 L a 2 L b 4 (GeMo12 O40 )] (8 ) (L a = 2, 3-diphenylpyrazine, L b = 2, 3-diphenylquinoxaline, C14 H10 O2 = 1, 2-diphenyl-ethane-1, 2-dione), were successfully synthesized by controlling the reaction parameters and well established by single-crystal X-ray diffraction, elemental analyses, and IR spectra. Compounds1–3 are based on theL a ligand, while4–6 are based onL b . The mixedL a /L b ligands induce the formation of7 and8 . In compound1, the linear [Ag4 L a 4 ] 4+ subunits link SiW12 anions to form a chain. Two adjacent chains connect each other through POM anion bonds and a screw-like double track is built. Compound2 is composed of 1D leaf-like Ag I -L a chains, which are further linked by anions to build a 2D grid-like layer. Compound3 was obtained under the same conditions as2 except at a different temperature. In3, the inorganic double chains are connected by linear metal–organic clusters [Ag3 L a 2 ] 3+ and a 2D layer is formed. Compounds4 and5 were also obtained at different temperatures. In4, the adjacent grid-like layers share the same Ag ions to construct a 3D framework. Compound5 is composed of 1D cycle-connecting-cycle chains, which are further linked by anions and Ag ions to build a 3D structure. Compound6 is a 3D framework, with dissociative anions accommodated in it. Compounds7 and8 are composed of mixed organic ligandsL a andL b . Compound7 has two kinds of chains, which are linked by anions to form a "ladder". Compound8 contains discrete anions and [Ag2 L a L b 2 ] 2+ units. The title compound modified CPEs can act as amperometric sensors for detecting hydrogen peroxide, potassium bromate and potassium nitrite. Compounds1–8 have excellent photocatalytic capacity for degradation of organic dyes MB and RhB under the sunlight irradiation.